Design and experiment of electro hydraulic active suspension for controlling the rolling motion of spray boom - Cui, Longfei; Xue, Xinyu; Le, Feixiang; Mao, Hanping; Ding, Suming (International Journal of Agricultural and Biological Engineering, 2019)
Boom sprayer is one of the most commonly used plant protection machinery for spraying pesticide. Studies have shown that the efficiency of chemicals is highly correlated with the uniformity of spray distribution patterns. As the boom is a large and flexible structure, boom rolling leads to overlapping and leakage of the pesticides. In order to improve spray uniformity, the boom attitude should be kept parallel to the ground slope or to the crop canopy beneath the boom. Passive suspension can attenuate frequencies above its resonance frequency, but nothing can be done to align the boom to the sloping ground. Therefore, an active suspension system is designed, which includes DSP-based controller, a servo valve, a hydraulic cylinder, two ultrasonic sensors, one inertial attitude sensor, and the developed control procedures. In order to prevent the wrong response of the control system caused by the high frequency component due to uneven crop canopy or rough ground. A special signal processing algorithm was proposed, including the limiting filter, smoothing algorithm and data fusion algorithm based on optimal weight. The transient and steady-state performances of the boom control system using velocity feedforward PID algorithm were tested on a six DOF motion simulator. It can be seen that the low-frequency tracking performance of the boom was greatly improved after the electro-hydraulic active suspension was added. At the resonance frequency, the peak angle of active suspension and passive suspensions are 0.72° and 1.29° respectively, and the resonance peak is greatly reduced. The controller was implemented on a self-propelled boom sprayer and validated under field conditions, the standard deviation of the roll angle of the boom with active suspension is 0.40°, compared with 1.04° of the sprayer chassis. Experimental results show that the active suspension control system can effectively reduce the effect of ground excitation disturbance on the application process, and has good tracking performance for low frequency terrain change.Keywords: boom sprayer, active suspension, electro-hydraulic servo system, six DOF motion simulator, signal process, motion controlDOI: 10.25165/j.ijabe.20191204.4648Citation: Cui L F, Xue X Y, Le F X, Mao H P, Ding S M. Design and experiment of electro hydraulic active suspension for controlling the rolling motion of spray boom. Int J Agric & Biol Eng, 2019; 12(4): 72–81.